Generational selling tactics that work : - Marston, Cam (John Wiley and Sons, 2011)
Highly energetic and engaging to read, Generational SellingTactics that Work is full of immediately actionable ideas foreach generation so you can sell confidently and deliver superbservice to each of these unique demographics.